지체장애인의 운동실천을 위한 동기면담 프로그램 개발 및 평가 - 정정희; 정인숙; Jeong, Jeong Hee; Jeong, Ihn Sook (Journal of Korean Academy of Nursing, 2017)
Purpose: The aims of this study were to develop a motivational interviewing program for exercise improvement in persons with physical disabilities and to examine the effect of this motivational interviewing intervention. Methods: The study employed a nonequivalent control group pretest and posttest design. A total of 62 persons with physical disabilities (30 in the experimental group, 32 in the control group) were recruited from 2 community rehabilitation centers. The experimental group received 8 sessions of a group motivational interviewing program, scheduled once a week, with each session lasting 60 minutes. Test measures were completed before the intervention, immediately after the end of the intervention, 2 weeks later, and 6 weeks after the end of the intervention. Measures included self-efficacy for exercise, decisional balance for exercise, stage of change for exercise, regularity of exercise, exercise maintenance, and independent living ability. Data were analyzed using the ${χ}^2-test$, Fisher's exact test, Independent samples t-test, and repeated measures ANOVA, conducted using IBM SPSS Statistics version 18. Results: The experimental group showed a significant increase in self-efficacy for exercise (F=50.98, p<.001), benefit (pros) of exercise (F=24.16, p<.001), and independent living ability (F=50.94, p<.001), and a significant decrease in loss (cons) of exercise (F=26.50, p<.001). There were significant differences between the two groups in stages of change for exercise (p<.001), regularity of exercise (p<.001), and exercise maintenance (${χ}^2=26.61$, p<.001). Conclusion: The motivational interviewing program has the potential to improve exercise levels in persons with physical disabilities.